2022
DOI: 10.3389/fpsyg.2022.874105
|View full text |Cite
|
Sign up to set email alerts
|

CEO Relational Leadership and Product Innovation Performance: The Roles of TMT Behavior and Characteristics

Abstract: CEO leadership is considered a critical antecedent of product innovation performance, but the relational aspect of leadership has been largely neglected in this area. Drawing on upper echelons theory and relational leadership literature, this study explores whether, how, and when CEO relational leadership influences product innovation performance. Specifically, we analyze the underlying mechanism of TMT (top management team) voice behavior and two boundary conditions—TMT educational level and TMT age. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Younger executives and older executives tend to differ in terms of management experience, risk preference, and information acquisition and processing [57][58][59]. As Hambrick and Mason (1984) have pointed out, age to some extent reflects an executive's experience and risk preference [39].…”
Section: The Moderating Effects Of Tmt Agementioning
confidence: 99%
See 3 more Smart Citations
“…Younger executives and older executives tend to differ in terms of management experience, risk preference, and information acquisition and processing [57][58][59]. As Hambrick and Mason (1984) have pointed out, age to some extent reflects an executive's experience and risk preference [39].…”
Section: The Moderating Effects Of Tmt Agementioning
confidence: 99%
“…Education can reflect the cognitive ability and knowledge range of executives to some extent [59,61,62]. Wiersema and Bantel (1992) have found that highly-educated TMTs are more willing to make strategic changes [63].…”
Section: The Moderating Effects Of Tmt Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…We measure this variable using some indicators such as: age (Wang et al, 2022), gender (Bsoul et al, 2022), educational background (Mukherjee & Sen, 2022), tenure (Huang et al, 2023) (Carmeli et al, 2012), work experience (Huang et al, 2023), ownership (Bsoul et al, 2022), and relational leadership (Wang et al, 2022). Age is an important indicator of CEO characteristics as it can influence their leadership style, decision-making, and experience.…”
Section: Introductionmentioning
confidence: 99%